Tracking trends in Arctic marine populations. ASTI Marine Report *Feb 2012 DRAFT*. - McRae, Louise; Deinet, Stefanie; Gill, Mike; Collen, Ben (CAFF International Secretariat, 2012)
Draft of the ASTI Marine Report "Tracking Trends in Arctic marine populations", submitted to the Arctic Council's Senior Arctic Officials meeting in Stockholm, Sweden, March 28-29 2012.